An in vitro evaluation of intravenous lipid emulsion on three common canine toxicants - Jones, Emery; Walton, Stuart A.; Davis, Jennifer; Council-Troche, McAlister (Frontiers in Veterinary Science, 2024)
ObjectiveTo determine whether intravenous lipid emulsion (ILE) therapy significantly reduces the concentration of baclofen, ibuprofen, and/or bromethalin in canine whole blood over time.AnimalsSeven 500 mL bags of canine DEA 1.1 negative blood were divided into aliquots of 125 mL and randomly assigned to one of three treatment groups (baclofen, ibuprofen, bromethalin) or four control groups (a positive control for each treatment group and a negative control group).ProceduresInjectable ibuprofen (200 mg/kg), baclofen (8 mg/kg), or bromethalin (3 mg/kg) was apportioned into 125 mL aliquots of canine whole blood and incubated for 30 min at 38.5°C. ILE (12.4 mL, Intralipid®) was added to each sample and the solution vortexed [215 rpm for 15 min at 37°C (98.6°F)]. Samples were obtained at designated time points (0, 15, 30, 60, 180, 360 min), centrifuged, and separated into serum and RBC fractions. Serum samples were ultracentrifuged (22,000 g for 10 min at 37°C) to separate lipid rich and poor fractions. Samples were stored at −80°C prior to analysis.ResultsA significant decrease in total drug concentration was established for bromethalin and its metabolite desmethylbromethalin compared to positive controls. ILE significantly reduced desmethylbromethalin at the 30-and 360-min time points. The remainder of the desmethylbromethalin time points did not reach significance. Bromethalin concentration was significantly reduced at all time points compared to positive controls. Neither baclofen nor ibuprofen had significant changes in concentration.ConclusionILE therapy was effective at reducing the total drug concentration of bromethalin and its metabolite desmethylbromethalin supporting the lipid sink theory. As a single compartment in vitro study, this study does not evaluate other proposed mechanisms of action of ILE therapy. ILE therapy may have other means of significantly decreasing lipophilic drug concentration in cases of toxicosis.